The occurrence of Enterobacteriaceae bacteria in feathers after slaughter of poultry - Cybulska, Krystyna; Mahdi OraibiMahdi Oraibi, Sanaa; Jakubowska, Barbara (Ecological Questions, 2018)
The Enterobacteriaceae family is a very diverse group of microorganisms. Especially, it contains in its composition a unit of a pathogenic nature causing serious illnesses and health problems of people and animals. They are a huge problem in the environment of animal husbandry, processing and waste management. The purpose of this work was to determine the amount of contaminants with Enterobacteriaceae bacteria species after the slaughter of different poultry species. The study used a pre-selective propagation technique on MacConkey’s liquid medium. To confirm the presence of Enterobacteriaceae bacteria, the inoculation onto VRBDA medium was made. The numbers of population and results of the tests allowed for calculating the MPN and the titre of tested bacteria group. Tested samples contained feather waste after slaughter of poultry, i.e. chickens, ducks, geese and turkeys. Material was collected at different dates from three poultry slaughterhouses in Western Poland. Based on the results obtained, the numerous presence of Enterobacteriaceae family bacteria has been confirmed in the waste feathers of various poultry species following the slaughter. The number of Enterobacteriaceae bacteria differed significantly in different materials and dates of measurement, which could be due to the heterogeneity of the animals supplied to the plants.